Interaksi Wisata Syariah dan Pembangunan Ekonomi di Kota Pusarnya Pulau Jawa dalam Bentuk Ekonomi Komersial Ganda - Endro Tri Susdarwono (Samarinda State Polytechnic, 2020)
The purpose of this study is to discuss the relationship or interaction between Islamic tourism and economic development in Pemalang Regency in the form of a double commercial economy. This research is a qualitative research, the type of research uses a comprehensive analytical study and analytical, normative approach. Sharia tourism must be understood as a religious and cultural concept, in which Islamic objectives, Islamic teachings, as well as Islamic principles and practices must be included and made into the programs offered in these Sharia tourism activities. This means that Sharia tourism is not only for moving the activities of tourists to our area, but also for offering them our religious and cultural values. I summarizes this conceptualization of Sharia tourism interactions in three main points: economy, culture and religion. Tourism is of course aimed as a business world that is halal and brings financial benefits to Muslims. Tourism can also be used as a medium to promote and introduce Islamic cultures. Finally, the interest of Islamic tourism is to spread Islamic values and teachings.